Rattus feliceus Thomas 1920 - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
695. Spiny Seram Island Rat Rattus feliceus French: Rat de Felix / German: Seram-Ratte / Spanish: Rata espinosa de Seram Other common names: Spiny Seram Rat Taxonomy. Rattus feliceus Thomas, 1920, Gunung Manusela, 6000ft (= 1830 m), Pulau Seram, Maluku (Moluccas), Indonesia. This species is monotypic. Distribution. Seram I, Moluccas, Indonesia. Descriptive notes. Head-body 167-287 mm, tail 165-185 mm, ear 20-22 mm, hindfoot 40-46 mm; weight 120-345 g. The Spiny Seram Island Ratis large, with spiny bicolored fur, white on belly and rufousbrown on back. It is characterized by dark tail 68-91%of head-body length; medium-sized hindfeet compared with head-body length; palatal bridge extending well beyond M?; well-developed temporal and postorbital ridges; wide and deep zygomatic notch; broad and medium-sized rostrum; lateral space between zygomatic root and maxillary and sphenoid bones; nearly flat top ofskull laterally between nasal and occipital; zygomatic arch nearly reaching orslightly reaching level of upper molar row ventrally; squamosal rootof zygomatic arch high on tympanic bulla; posterior palatine foramina at M” level; moderately developed jugular process; in palatal view, squamosal root of zygomatic arch reaching level of small and not inflated tympanic bulla; in palatal view, zygomatic rootof zygomatic arch overlapping at level of molar row; slightly developed eustachian tube; post-glenoid vacuity fused with middle lacerate foramen; basisphenoid that seems suspended in spheno-palatine vacuity; posteriorly, long incisive foramina reaching level offirst upper molar; wide angular process not extending beyond posterior part ofarticulation condyle; orange, opisthodont, and large incisors; wide incisor blade equal or larger in size to its longest basal width; no cusp t7 on M'; postererocone forming little bulge on M'; cusp t3 present on M? and M? no tl bis on M'; cusp tl of M' behind cusps t2 and t3, forming bulge on first M' lamina; well-developed cusp t8 of M' and M? compared with other cusps, forming ...